The Use of the Quantum Teaching Method to Improve Learning Outcomes of the Al-Qur'an and Hadith Subject for Class IX.6 Students - An'nisa Miranti Amri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to determine the learning outcomes of the Al-Qur'an Hadith of class IX.6 students before using the quantum teaching method, the learning outcomes of the Al-Qur'an Hadith of class IX.6 students after using the quantum teaching method, and the differences in learning outcomes of class IX.6 students before and after using the quantum teaching method. Methodology: The type of research used was Pre-Experimental with a One Group Pre-Test - Post-Test design. The sample of this research was class IX.6 as an experimental class totaling 25 students without a control class. Main Findings: The study concluded that student learning outcomes before using the quantum teaching method were in the